2008
DOI: 10.2147/cia.s1880
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic pain in the elderly: focus on transdermal buprenorphine

Abstract: Chronic pain in the elderly is a signifi cant problem. Pharmacokinetic and metabolic changes associated with increased age makes the elderly vulnerable to side effects and overdosing associated with analgesic agents. Therefore the management of chronic cancer pain and chronic nonmalignant pain in this growing population is an ongoing challenge. New routes of administration have opened up new treatment options to meet this challenge. The transdermal buprenorphine matrix allows for slow release of buprenorphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 78 publications
1
57
0
1
Order By: Relevance
“…Buprenorphine transdermal patches, which are available in low doses, fit the guideline recommendations in this respect. Buprenorphine patches are considered to be a suitable pain relief among elderly patients compared with other low/high potency opioids due to the pharmacokinetic profile and pharmaceutical form of administration, since no dose adjustment is needed for elderly patients 21,22 or patients with impaired renal function [23][24][25] , and because buprenorphine has been shown to have a favorable safety profile compared with other opioid analgesics 26 . Buprenorphine pharmacokinetics are also stable in patients with mild to moderate hepatic impairment 27 .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%
“…Buprenorphine transdermal patches, which are available in low doses, fit the guideline recommendations in this respect. Buprenorphine patches are considered to be a suitable pain relief among elderly patients compared with other low/high potency opioids due to the pharmacokinetic profile and pharmaceutical form of administration, since no dose adjustment is needed for elderly patients 21,22 or patients with impaired renal function [23][24][25] , and because buprenorphine has been shown to have a favorable safety profile compared with other opioid analgesics 26 . Buprenorphine pharmacokinetics are also stable in patients with mild to moderate hepatic impairment 27 .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%
“…37 Buprenorphine is also excreted primarily in the feces and is considered safe in persons with renal impairment. 38 Assessment and management of opioid-related risks and side effects One common reason cited for noncompliance with opioid therapy is the fear of side effects. The side effects of most concern include constipation, nausea and vomiting, sedation, confusion, and respiratory depression.…”
Section: Opioid Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…Also of importance in the elderly, the plasma concentration of buprenorphine does not increase in patients with chronic renal disease or decrease in patients receiving hemodialysis. 23,24 This is particularly relevant to the treatment of elderly individuals with dementia, as studies have indicated that improved pain management may decrease agitation and other mood symptoms in those with dementia, many of whom might otherwise have received antipsychotic medicines. 23,25 Contraindications to use of buprenorphine include paralytic ileus, severe respiratory disease, or severe hepatic disease.…”
Section: Buprenorphine (Butrans)mentioning
confidence: 99%